Root-knot nematode assessment: species identification, distribution, and new host records in Portugal - Rusinque, Leidy; Camacho, Maria João; Serra, Clara; Nóbrega, Filomena; Inácio, Maria L. (Frontiers in Plant Science, 2023)
Considered one of the most devastating plant parasitic nematodes worldwide, Meloidogyne sp. (commonly known as the root-knot nematodes, RKN) are obligate sedentary endoparasites that establish in the roots causing hyperplasy and hypertrophy of surrounding cells triggering the formation of galls. These galls will affect root development and physiology, leading to substantial yield losses. During 2017-2022 an extensive survey of Meloidogyne species was undertaken in Portugal (mainland and islands). A total of 1071 samples were collected by the National Plant Protection Organization (DGAV) and private farmers from different regions of the country and were analysed at the Laboratory of Nematology (NemaINIAV). Samples where the presence of Meloidogyne sp. was detected, were used to perform bioassays to obtain females and juveniles for further studies. Since the accurate identification of RKN is an important aspect of crop management, morphological and biochemical characterisation was performed. The most common morphological features were observed, showing consistency with previous descriptions of the genus. The biochemical identification using the esterase (EST) phenotype revealed the phenotypes of Meloidogyne arenaria, Meloidogyne enterolobii, Meloidogyne hispanica, Meloidogyne hapla, Meloidogyne incognita, Meloidogyne javanica and Meloidogyne luci. Meloidogyne incognita and M. javanica were found to be the most prevalent species in the different regions followed by M. arenaria and M. hapla. This is the first distribution report performed in Portugal on RKNs, contributing to the development of management strategies and to updated information on the status of these pests in Europe.